2017
DOI: 10.1192/bjp.bp.116.193920
|View full text |Cite
|
Sign up to set email alerts
|

The use of community treatment orders in competent patients is not justified

Abstract: Empirical evidence for the effectiveness of community treatment orders (CTOs) is at best mixed. We examine CTOs through the prism of human rights and discrimination, bearing the evidence in mind, and argue that a necessary condition for their use is that a person lacks decision-making capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…12,13 Such concern has come to particular prominence in recent years with the advent of the United Nations Convention on the Rights of Persons with Disabilities. 14,15 This disquiet around coercion has been heightened by conflicting research evidence about the effectiveness of CTOs. 16 Although some studies have found positive outcomes for patients, others have not.…”
Section: Community Treatment Orders: a Global Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Such concern has come to particular prominence in recent years with the advent of the United Nations Convention on the Rights of Persons with Disabilities. 14,15 This disquiet around coercion has been heightened by conflicting research evidence about the effectiveness of CTOs. 16 Although some studies have found positive outcomes for patients, others have not.…”
Section: Community Treatment Orders: a Global Phenomenonmentioning
confidence: 99%
“…Time_Group Re-admission Censored CTO Censored, censorship status (0 = not censored, 1 = censored); CTO, CTO status (0 = control group patient, 1 = treatment group patient); Re-admission, re-admission status (0 = not re-admitted, 1 = re-admitted); Time_Group, time to re-admission or censorship in 90-day periods for the 4-year study period (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Appendixmentioning
confidence: 99%
“…However, competent patients are not necessarily good candidates for a CTO. Patients with DMC have adequate insight to opt for voluntary community treatment without a CTO (Newton-Howes & Ryan, 2017). However, it is worth noting that while a patient's DMC puts them in a better position, insight is not necessarily connected with treatment adherence, especially if the patient has a history of high-risk behaviour or has a severe relapse profile (Dawson & Mullen, 2008).…”
Section: Factors That Influence Outcomes Of Ctosmentioning
confidence: 99%
“…The need for support may still be high and services like intensive case management (ICM) or assertive community treatment (ACT) may have to be put in place (15). However, compulsory community treatment, which in the UK or the US often combines with ICM or ACT (16) would not be consistent with the principle of Article 12 of the CRPD.…”
Section: Psychosismentioning
confidence: 99%